2021
DOI: 10.1177/10998004211022849
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Interventions to Improve Psychosocial Aspects and Glycemic Control in Type 2 Diabetic Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Type 2 diabetes mellitus (T2DM) patients have a raised risk of developing depression compared with non-diabetic people. Objective: The objective of this meta-analysis was to investigate the impacts of exercise training interventions to improve psychosocial aspects and glycemic control in T2DM patients. Data sources: PubMed, CINAHL, Medline, Google Scholar, and Scopus databases and reference lists of included studies were searched. Study selection: The selection criteria were randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Both study groups demonstrated improvement in mental well-being outcomes at the study endpoint, although the intervention effect was not statistically significant. Preliminary findings of this study suggest that women’s exposure to self-monitoring of physical activity and lifestyle behavior may have improved their mental well-being over time ( 30 ). In addition, health concerns related to glucose intolerance are often attributable to physiological and psychological stressors.…”
Section: Discussionmentioning
confidence: 88%
“…Both study groups demonstrated improvement in mental well-being outcomes at the study endpoint, although the intervention effect was not statistically significant. Preliminary findings of this study suggest that women’s exposure to self-monitoring of physical activity and lifestyle behavior may have improved their mental well-being over time ( 30 ). In addition, health concerns related to glucose intolerance are often attributable to physiological and psychological stressors.…”
Section: Discussionmentioning
confidence: 88%
“…Individuals diagnosed with DM are recommended to maintain 150 minutes of moderate-intensity or 75 minutes of high-intensity aerobic exercise per week, or a combination of both recommendations. In addition, these individuals should do exercises to increase their muscle strength at least 2 days a week [6,7]. Since the effect of the exercise lasts for 24-72 hours, it is stated that individuals with DM can take a break from their exercises for a maximum of two consecutive days [4].…”
Section: Introductionmentioning
confidence: 99%